Poincare type inequalities of Heisenberg group target for p < 2 - Jia, Gao; Li, Fang-lan (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we prove some Poincare type inequalities of the Heisenberg group target space in the case of 2mm+1 p < 2. In order to overcome the obstacles which are due to the nonlinear structure of the group laws, there are some techniques in the arguments for proving the results.